The Influence Of Innovation Strategy On MSME Performance With Green Innovation As A Mediating Variable: Study Of Food And Beverage MSMES In Mojokerto Regency - Nafisah, A’isy Fiklil; Sudarto, Triadi Agung; Maharani, Satia Nur (International Journal of Business, Law, and Education, 2023)
Many companies only prioritize product innovation to meet current consumer needs and are able to generate profits without paying attention to the impact of production activities on the environment. In the last few decades, environmental damage has become an important issue that is often discussed. This is because environmental damage occurs more frequently, such as forest fires, air and water pollution, extreme drought, erratic climate change and so on. One of the environmental damage factors that occurs is caused by economic growth which causes the exploitation of energy and natural resources to increase due to production needs. Development in the economic sector continues to be carried out with the aim of improving the welfare of Mojokerto residents. Not only that, the development carried out also aims to increase community competitiveness in the economic sector. Mojokerto has an MSME sector which operates in a number of fields. MSMEs or Micro, Small and Medium Enterprises are economic businesses owned by individuals or business entities that have been determined by law. The food businesses in Mojokerto are quite varied, some produce semi-finished ingredients, some also produce finished products. The type of research used in this research is explanatory research. In this study, The population in this study is the total number of Food and Beverage MSMEs registered with the District Industry and Trade Service. Mojokerto. and there were 100 samples in this study. The sampling technique used in this study was purposive sampling. The analysis technique in this study used the PLS technique. Conclusion: Green Innovation has a positive and significant influence on MSME performance. Innovation Strategy has a significant positive influence on Green Innovation. Innovation Strategy does not have a significant positive influence on MSME Performance. Innovation Strategy has a significant positive influence on MSME Performance through Green Innovation of MSMEs